Kualitas Fisik, Populasi Aspergillus flavus, dan Kandungan Aflatoksin B1 pada Biji Kacang Tanah Mentah - Okky Setyawati Dharmaputra; Santi Ambarwati1; Ina Retnowati; Amanda Windyarani (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
The objective of this study was to investigate the physical quality, Aspergillus flavus population and aflatoxin B1 content of raw peanut kernels collected from retailers in two traditional markets (pasar Anyar and pasar Bogor) in the city of Bogor in August 2009. The number of samples collected from pasar Anyar and pasar Bogor was 14 and 12, respectively. Physical quality of kernels was determined based on the percentage of intact, shriveled and damaged kernels. Damaged kernels consisted of broken and damaged kernels caused by insect or fungal attack. Aspergillus flavus population was determined using serial dilution method followed by pour plating method on aspergillus flavus and parasiticus agar. Aflatoxin B1 content was determined using thin layer chromatography method. The results showed, that the mean of percentage of intact, shriveled and damaged kernels of peanuts collected from pasar Anyar was 70.6, 12.3 and 17.1%, respectively; while that of collected from pasar Bogor was 60.2, 12.7 and 27.1%, respectively. The mean of A. flavus populations in peanuts collected from pasar Anyar and pasar Bogor was 8194 cfu g-1 and 983 cfu g-1, respectively. The mean of aflatoxin B1 content in peanuts collected from pasar Anyar and pasar Bogor was 2.0 ppb and 91.4 ppb, respectively. The percentage of peanut samples containing aflatoxin B1 more than 15 ppb and collected from pasar Anyar and pasar Bogor was 7.1% and 25%, respectively.